Diversity of the Aquatic Vegetation in the Irrigation Canals of Mulya Sari village, Banyu Asin Regency, South Sumatra - Wiwik Septiani; Siti Masreah Bernas; Yuanita Windusari (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2018)
Mulya Sari village in Banyuasin Regency is a sub-optimum tidal land with sulfuric acid characteristics which utilize irrigation canal to provide water used in household, fishing, and agriculture. Information on the diversity of aquatic vegetation in the Mulya Sari village is still not much. The purpose of this research to identified and analyzed the diversity aquatic vegetation in the irrigation canal of Mulya Sari village. The method used in this research is purposive sampling method. Aquatic vegetation data are collected trough direct study and using the square of the wooden frame size of 1 m x 1 m (transect methode), then observation are made for identification. Environmental condition in the irrigation canal is still good, with the environmental parameters in the form of Temperature, DO, BOD, TSS, TDS and pH still meet environmental quality standard. The irrigation canal in Mulyasari village was found 7 species of aquatic vegetation belonging to 3 class of Liliopsida, 3 class Monocotyledoneae, and 1 class of Dicotyledoneae, with the value of diversity index between 0,57 – 1,53 and low diversity. Corellation Pearson between water quality and sediment characters of diversity has shown Temperature, DO, BOD, TDS and pH have corellation to diversity.